Red America, Blue America? It Might Be Mostly Race - Easton, Abigail M. (My University, 2020)
One of the most critical influences in American voting behavior is the political split between urban, suburban, and rural areas. Political analysts have discussed the importance of understanding the differences in ideological regions to be able to predict what party will win the majority in the states and what seats that party will win. However, there is not enough research available to be able to understand this political split and the effect that it can have on national elections. Because of this lack of available data for the most recent presidential election, this paper will show the survey analysis from ANES Time Series study 2012. Using SPSS, the available urban/rural split data will be compared with a number of variables including votes, race, gender, age, etc. The original proposal of this paper was to examine the rural/ urban split in American party politics, but when examining the data, a stronger and more interesting relationship came out of the data. Namely that the 2012 election abandoned all traditional voting norms and instead focused on cultural differences between the candidates, essentially proving that the 2012 election was all about race.